Artemisia annua L.: produção de biomassa, artemisinina, rendimento e composição de óleo essencial influenciados por diferentes eliciadores e níveis de adubação NPK - Paladini, Marcos Vily (2012)
Artemisia annua L. is an herbaceous annual plant, originally from China and acclimatized to Brazil, which produces artemisinin, a sesquiterpene lactone used in the treatment of malaria. The species is the only economically viable source of this molecule. Also, it is a highly aromatical species and it produces great amount of essential oil, rich in terpenes. This work has as objective to determine the influence of elicitor molecules and levels of NPK fertilizer in the biomass production, artemisinina and composition of the essential oil in the variety of Artemis A. annua, produced in the field in the town of Pato Branco. An experiment with fertilization was conducted in the field during the years of 2008 and 2009, where plants of A. annua were submitted to increasing levels of NPK chemical fertilizer in a ground of average fertility. From the standard dose of fertilizer (N: 160 kg ha-1; P2O5: 175 kg ha-1; K2O: 90 kg ha-1) it was defined the half dose treatments, one dose and two doses, beyond the control treatment, in the formulations Urea, Super Simple Phosphate and Potassium Chloride. Another experiment with eliciation was lead, where plants of A. annua were submitted to the elciation with acibenzolar-S-methylic and two products harpin-protein based, by means of three weekly sprayings, since the beginning of the floral induction period up to one week before the harvest. In both experiments, the material was dried and separated, the quantification of artemisinin was carried through by thin layer chromatography with detection by densitometry. The chemical profile of the oil was determined by gas chromatography. In the fertilization experiment the dry masses of stalk, aerial part and the relation stalk-leaf had an adjustment for a linear equation, with the best results for the treatment two times the dose: 10,43 t ha-1, 14.21 t ha-1, respectively for dry masses of stalk and aerial part, and greater relation stalk-leaf (0,4) for test treatment. The variable leaf dry mass got an adjustment for second degree equation, with maximum efficiency technique in 1,57 doses and estimated yeld of 3,87 t ha-1. The influence of NPK fertilizer doses on the artemisinin content (average 5,98 kg t-1) and the artemisinin productivity (average 19,45 kg ha-1) did not present significant adjustments for straight line. Twenty-eight components were identified in the essential oil chemical profile that comprise 94.96%. The majoritarian substances were camphor (44.75%), 1,8 cineole (7.90%), γ-muurolene (6.75%), trans-β-farnesene (6.51%), mircene (5.74%). Seven components of the essential oil showed variation in function of NPK fertilizer levels: p-cymene, camphene, trans-β-terpineol, α-pinene, viridifloreno, acetate of mirtenila and β-pinene, the relative content of these components varied from 0,53 to 2.23% representing about 8% of the essential oil profile. The predominant class was of monoterpenes (72%). In the experiment with eliciation, the elicitors acibenzolar-S-methylic and harpin protein did not result in significant alterations in the leaf, stalk, aerial part biomasses and in the relation stalk-leaf of A. annua; as well as they did not show differences in the artemisinin and essential oil contents and yeld. In the chemical profile 31 components were identified, which comprise 91.5% of the essential oil. The treatments with the elicitors acibenzilar-S-methylic and harpin did not result in significant differences for any of the identified and quantified substances. The majoritarian components were camphor (43.38%), 1,8 cineole (9.28%), mircene (7.69%) γ-muurolene (5.00%), camphene (4.54%) trans-β-farnesene (3.98%). Monoterpenes were the predominant class in the essential oil (79.8%).